Análisis de brechas del perfil profesional del personal de la Cooperativa de Ahorro y Crédito Calceta Ltda. para definición del plan de capacitación. - Loor Montes, Andrea Michelle (2018)
This research had as objective analyze the gaps in staff of Cooperativa de Ahorro y Crédito Calceta Ltda. professional profile to define a training plan according to the needs of workers, where it was essential the use of techniques such as the interview which was directed to the General Manager and the head of human resources for information about how to set the staff training needs, what are the measures taken to mitigate the gaps between the profile of the position and the selected person stressing was also made a comparison between the actual profile of the employee and required by since, with the use of a tab's observation also applied an array of analysis of gap covering the evaluation of education, labor, and experience of the main indicators of performance, in which it was able to identify that this entity has with 79 employees distributed in different agencies in the province, 55% of them comply fully with the requirements for the post while 19% which corresponds to 15 employees have small flaws in certain skills and knowledge that can be countered through training. The training plan is aimed at settling the existing gap between the post and the employee's profile and thereby contribute to reach the levels of efficiency of the Organization and at the same time have a highly competent staff.